2017
DOI: 10.1016/j.acra.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Independently Associated with Increased CT Scan Lung Density

Abstract: Rationale and Objectives Non-infectious pulmonary complications are common among HIV-infected individuals and may be detected early by quantitative CT scan. The association of HIV disease markers with CT lung density measurement remains poorly understood. Materials and Methods 125 participants free of spirometry-defined lung disease were recruited from a longitudinal cohort study of HIV-infected and HIV negative individuals to undergo standardized CT scan of the chest. Parenchymal densities for the entire lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…18 Several studies have reported higher lung densities on CT imaging in people living with HIV versus controls, suggesting interstitial pulmonary pathology. 7,19 However, CT imaging studies evaluating never-smokers or adolescents with HIV have shown that both airway disease in general as well as small airway disease specifically were more frequently observed in HIV-positive participants compared with controls. [19][20][21] Importantly, these studies have been crosssectional in design and reflect not only recent and ongoing HIV-related damage, but also historical tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Several studies have reported higher lung densities on CT imaging in people living with HIV versus controls, suggesting interstitial pulmonary pathology. 7,19 However, CT imaging studies evaluating never-smokers or adolescents with HIV have shown that both airway disease in general as well as small airway disease specifically were more frequently observed in HIV-positive participants compared with controls. [19][20][21] Importantly, these studies have been crosssectional in design and reflect not only recent and ongoing HIV-related damage, but also historical tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies evaluating airway obstruction or emphysema have been less consistent in showing differences between people living with HIV on cART and uninfected controls. [5][6][7] Disentangling the ongoing effects of suppressed HIV infection on pulmonary health from those effects related to previously untreated HIV infection and historical risk behaviours remains challenging, mainly because most studies evaluating such differences have been crosssectional in design. In a previous cross-sectional analysis of baseline data from the AGE h IV cohort, we showed that HIV-positive participants reporting less than 25 pack-years of cumulative smoking had a lower forced vital capacity (FVC) but a similar forced expiratory volume in 1 s (FEV 1 ) compared with HIV-negative participants with similar smoking exposure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quantitative measurements correlate better with microscopic and macroscopic emphysema than visual scoring [34], may be less prone to over-estimating the extent of emphysema [32] and provide better reproducibility [35]. Few quantitative CT studies have been performed in PLWH [14,15,36,37]. The largest of these studies was the Lung-HIV study from three US centres performing quantitative emphysema determination in 510 PLWH [14].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have included uninfected controls. One study compared mean lung density, but not specific %LAA-950 thresholds, in 83 PLWH and 42 uninfected controls, and found HIV to be independently associated with higher lung density [37]. These findings may suggest other underlying disease processes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scan is used to evaluate curative effects and predict prognosis mainly from tumor size and morphological changes, but its accuracy is not high. Diffusion-weighted imaging (DWI) is used to evaluate curative effects from tumor molecular or cell level changes, and its apparent diffusion coefficient (ADC) can provide quantitative indicators for esophageal cancer before and after treatment, thus predicting the curative effect more accurately in an earlier stage ( 4 , 5 ). In this study, the diagnosis and treatment of esophageal cancer were analyzed via CT scan and magnetic resonance imaging (MRI) scan for patients with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%